Application of the Modified PLUM Method to a Dense Seismic Intensity Network of a Local Government in Japan: A Case Study on Tottori Prefecture - Kagawa, Takao (Frontiers in Earth Science, 2021)
An application of PLUM (Propagation of Local Undamped Motion) method to real time seismic intensity distribution from dense seismic intensity network maintained by a local government in Japan is demonstrated. JMA (Japan Meteorological Agency) has employed PLUM method from March 2018 as a supplement to the traditional EEW (Earthquake Early Warning) requires epicenter determination. Dense observation network is desirable for upgrading accuracy and quality of EEW including PLUM method. Seismic intensity meters in Tottori prefecture Japan are suitable for the purpose because they have been improved to broadcast packets with peak ground acceleration and JMA seismic intensity at every one second. Also, we can use 34 seismic intensity meters in the target area but only 6 observation sites are used for the EEW by JMA. The data are received at Tottori University and modified PLUM method considering wave propagation with damping not only from the observation points but also all evaluating points at 1 km mesh. Additionally, P wave amplitudes in preliminary tremors are also introduced to estimate seismic intensities from an empirical relationship. Applying the methodology to past earthquake data, it is confirmed that more detailed and rapid grasp of seismic intensity distribution is achieved. We expect the system will be utilized for earthquake disaster mitigation measures of local governments.